(untitled) (Archives of Pediatrics of Uruguay, 2021)
We present the first three pediatric patients transported by helicopter with severe cranioencephalic trauma assisted at our institution. The assistance protocol used in our Hospital for the reception, stabilization and timely transfer is shown after coordination with public and private health providers. Informed consent was requested from the children’s parents for the use of the data in scientific activities and publications.